APPLICATION OF NATURAL ENVIRONMENT APPROACHES TO IMPROVE SCIENCE PROCESS SKILLS IN ELEMENTARY SCHOOL STUDENTS - Fajari, Laksmi Evasufi Widi; Joharman, Joharman; Salimi, Moh (Universitas Sebelas Maret, 2018)
The purpose of this research is to describe the implementation of Natural Environment Approach (PLAS) to improve the science process skill in elementary school students. This classroom action research is a collaborative study conducted by teachers and prospective teachers. The subjects of this study were teachers and students of class V. The results showed that the application of PLAS can improve the science process skill through the steps of: (1) determining the learning objectives, tools and instruments needed, and instructional activities, (2) the students are divided into several groups, (4) investigating and observing objects, discussing task sheets, and recording information, (5) reporting findings, (6) conclusions and evaluations of learning.